TRANSFORMASI STRATEGI PEMBELAJARAN DI ERA DIGITAL: INOVASI MENUJU PENDIDIKAN ABAD 21 - Kuwat, Rahmadi; Haris Fadhilah; Yatin Mulyono (Jurnal Metabio, 2025)
The transformation of learning strategies in the digital era has become a critical necessity to meet the demands of 21st-century education. This study employs a meta-analysis method to examine the effectiveness of various digital learning strategies on student learning outcomes and 21st-century skills. Data were collected from eight SINTA-indexed articles published between 2018 and 2024, using experimental and quasi-experimental research designs. The analysis revealed that most digital strategies produced a Cohen’s d value greater than 0.8, indicating a large to very large effect. Strategies such as blended learning, flipped classroom, problem-based learning (PBL), and the integration of STEM–TPACK proved effective in enhancing learning achievement, digital literacy, critical thinking, and collaboration skills. These findings affirm that digital-based learning is not merely a technological adaptation but a strategic pedagogical innovation to develop learners who are ready to face global and digital era challenges. Keyword: Digital learning strategies, meta-analysis, Cohen’s d, 21st-century skills, educational innovation, digital literacy, STEM–TPACK.